Konsep dan Penerapan Model Kebijakan Corporate Environmental Responsibility di Indonesia - Isnaini, Syamsudin; Diamantina, Amalia (Fakultas Hukum Universitas Bangka Belitung, 2020)
The friction between economic interests and environmental interests has become a serious problem today. The friction between the two interests is evident in the activities of a company, therefore a company is given responsibility for the impact caused by its activities. This responsibility is “corporate social and environmental responsibility”. However, the term